The association of missed nursing care and determinants of satisfaction with current position for direct‐care nurses—An international study - Bragadóttir, Helga; Burmeister, Elizabeth A.; Terzioglu, Fusun; Kalisch, Beatrice J. (Journal of nursing management, 2020)
Aim To describe the association of missed nursing care and to identify the determinants of satisfaction with current position for direct‐care nurses. Background Missed nursing care and job satisfaction are important issues regarding quality patient care and safety in health care, globally. Method This was a cross‐sectional quantitative study using MISSCARE Survey data. Participants were 7,079 nursing staff providing direct patient care in hospitals in Australia, Iceland, Turkey and the USA. Multivariable nested models were used to identify the relationship between missed nursing care and nurses’ satisfaction with current position. Results More missed nursing care was associated with less satisfaction with current position. Other determinants of job satisfaction included country, nursing experience, overtime worked, adequacy of staffing and the number of shifts missed during the previous 3 months. Conclusion(s) Internationally, more missed nursing care is associated with less nursing job satisfaction and is influenced by work experience, overtime worked, levels of staffing and absenteeism. Implications for Nursing Management This study identifies that the association between missed nursing care and satisfaction with nursing position is of global concern. Other factors requiring the attention of nurse managers are staffing levels, absenteeism and work experience.